A practical application of sensory and rheological measurement in the development of fish pâté quality attributes - Ranilović, Jasmina (Array, 2020)
The flavor and texture of fish pâté are the most important attributes for consumers. The aim of the study was to analyze and compare commercial fish pâté with a laboratory prototype by combining sensory and rheological measurements. Quantitative Descriptive Analysis and Texture profile were established by expert sensory panelists, while the texture was additionally examined through rheological measurement. The results show a statistically significant difference between samples in relation to four flavor characteristics (color, fish odor, flavor saltiness, p <0.05) and five texture characteristics (surface, plasticity, spreadability, density, graininess, p <0.05). Regarding texture profile, the commercial fish pâté showed firmer density, and spreadability than does the laboratory prototype. Sensory and rheological data for both samples were highly positively correlated. Although the laboratory prototype has reached a certain level of desirable characteristics of fish pate (color, taste, spices) the acceptability of the observed differences in texture should be examined on a representative sample of consumers.